Improved microwave absorption and EMI shielding properties of Ba-doped Co–Zn ferrite. Issue 3 (1st February 2022) - Batoo, Khalid Muajsam; Hadi, Muhammad; Verma, Ritesh; Chauhan, Ankush; Kumar, Rajesh; Singh, Mahavir; Aldossary, Omar M.
Abstract: Herein, we report the synthesis of Ba-doped Co–Zn ferrite nanoparticles using the sol-gel auto combustion technique. The single-phase formation of the samples with F d 3m space group was confirmed by X-ray diffraction (XRD). The crystallite size, lattice parameter, and x-ray density, decreases with increasing dopant concentration. Scanning Electron Microscopy (SEM) shows the formation of irregular grains for all the samples. The oxidation states of Ba, Co, Zn, Fe, and O were estimated using X-ray photoelectron spectroscopy (XPS), which confirmed the chemical purity of the samples. Cationic distributions at tetrahedral and octahedral sites were proposed based on XPS studies. Fourier transformation infrared (FTIR) spectra shows the presence of two strong peaks around 430 cm −1 and 580 cm −1 that confirmed the formation of ferrite structure. The M − H curves were acquired to analyze the magnetic ordering in the specimens where the highest saturation magnetization (Ms) value of 43.479 emu/g was witnessed for x = 0.05. The microwave properties shows a decrease in magnetic loss and dielectric loss from 0.486 to 0.319 and 0.178 to 0.168 when Ba concentration was increased. EMI shielding analysis shows an increase in effective shielding ( S E T ) from 11.43 dB to 12.82 dB.